Diagnosis dan Tata Laksana Akantosis Nigrikans: Tinjauan Pustaka - Sibarani, Benly Levi Andreas; Putri Utami (Cermin Dunia Kedokteran, 2026)
Acanthosis nigricans (AN) is a skin disorder characterized by hyperpigmented, thickened, and velvety lesions, primarily affecting intertriginous areas. This condition is commonly associated with insulin resistance, diabetes mellitus, obesity, endocrine disorders, and the use of certain medications, and in some cases may serve as a marker of underlying internal malignancy. Individuals with darker skin are more prone to developing AN. Although it can be present at birth, AN is more commonly observed in adults. This literature review aims to discuss the etiology, pathomechanism, clinical manifestations, diagnostic approach, and management of acanthosis nigricans, with emphasis on its role as an indicator of underlying systemic disease. Literature was obtained from various relevant scientific sources, including review articles, case reports, and clinical studies. The pathogenesis of AN is primarily associated with hyperinsulinemia, which stimulates keratinocyte and fibroblast proliferation through the insulin-like growth factor-1 (IGF-1) pathway. Diagnosis is generally established clinically, although laboratory and histopathological evaluations may be required in certain cases. Management focuses on treating the underlying condition, such as weight reduction, improvement of insulin resistance, and management of malignancy when present, along with topical or procedural therapies to improve skin lesions and patients’ quality of life.